2015
DOI: 10.1016/j.chemgeo.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Subduction zone metamorphic pathway for deep carbon cycling: II. Evidence from HP/UHP metabasaltic rocks and ophicarbonates

Abstract: Exposures of low-grade metabasalts and ophicarbonates in the Northern Apennines, and their high- and ultrahigh-pressure metamorphic equivalents in the Western and Ligurian Alps and Tianshan (representing an overall peak P- T range of ~ 0.2-3.0. GPa, 200-610. °C), allow investigation of the effects of prograde metamorphic devolatilization, and other fluid-rock interactions, on degrees of retention and isotopic evolution of C in subducting oceanic crust and associated mantle rocks. Such work can inform models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 153 publications
9
102
0
Order By: Relevance
“…Comparison of δ 13 C and δ 18 O of calcite veins and marble/calcsilicates from the ASZ (see data in Table S3) with values for calcite in other HP lithologies in the Penninic domain, including the Zermatt‐Saas unit ( ZSU ) and the Monviso massif ( MV ; data from Cook‐Kollars et al ., ; Collins et al ., ). The grey arrow indicates the trajectory in O and C isotope compositions followed by a rock undergoing decarbonation by a Rayleigh process.…”
Section: Carbon and Oxygen Isotope Compositions Of Asz Carbonatesmentioning
confidence: 54%
See 1 more Smart Citation
“…Comparison of δ 13 C and δ 18 O of calcite veins and marble/calcsilicates from the ASZ (see data in Table S3) with values for calcite in other HP lithologies in the Penninic domain, including the Zermatt‐Saas unit ( ZSU ) and the Monviso massif ( MV ; data from Cook‐Kollars et al ., ; Collins et al ., ). The grey arrow indicates the trajectory in O and C isotope compositions followed by a rock undergoing decarbonation by a Rayleigh process.…”
Section: Carbon and Oxygen Isotope Compositions Of Asz Carbonatesmentioning
confidence: 54%
“…Collins et al . () suggested that the low δ 18 O values for some particularly highly‐veined ZSU (and Monviso) metabasalts and ophicarbonates could reflect infiltration of the rocks by an H 2 O‐rich fluid with δ 18 O as low as +6.0‰ sourced in the slab mafic/ultramafic section. An H 2 O‐rich fluid equilibrated with a clinopyroxene/garnet source lithology (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Exhumed metamorphic terranes provide essential insights into the mechanisms of deep carbon recycling and mobilization in subduction zones (Bebout & Penniston‐Dorland, ; Ferrando, Groppo, Frezzotti, Castelli, & Proyer, ; Piccoli et al., ; Scambelluri et al., ). Thermodynamic calculations and studies of eclogite facies marbles and carbonated eclogites and serpentinites in palaeo‐subducted metamorphic terranes show that carbonate minerals undergo variable extents of decarbonation and can be stable at high pressure (Collins et al., ; Connolly, ; Cook‐Kollars, Bebout, Collins, Angiboust, & Agard, ; Ferrando et al., ; Proyer, Mposkos, Baziotis, & Hoinkes, ). Studies of natural examples of HP metamorphism of carbonate‐bearing rocks during Atg‐serpentinite dehydration are scarce and limited to assess the mass‐balance of carbon during dehydration (Alt et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Compilation of peak pressure–temperature (P–T) conditions of meta‐ophicarbonates (white fields) superposed on the pseudosection of a Ca‐bearing serpentinite from the Almirez massif. VM : Voltri massif (Scambelluri et al., ); ZS : Zermatt‐Saas; B: Bracco Unit, Internal Ligurides; UV : Ubaye Valley, Western Alps (all from Collins et al., ). L, L*: Lanzo massif peak conditions and PT of graphite‐formation in ophicarbonate, respectively (Vitale Brovarone et al., ); BA : contact‐metamorphic ophicarbonates, Bergell aureole (Pozzorini & Früh‐Green, ; Trommsdorff & Connolly, ); BD : Bellinzona‐Dascio unit, Central Alps (Stucki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon transfer in subduction zone fluids is induced by decarbonation or dissolution processes (Ague & Nicolescu, ; Gorman et al, ; Kelemen & Manning, ; Kerrick & Connolly, , ). However, carbonates can remain stable to very high pressures and temperatures in subduction zones, resulting in inefficient decarbonation in forearcs (Collins et al, ; Dasgupta & Hirschmann, ; Kerrick & Connolly, ; Molina & Poli, ; Poli et al, ; Thomsen & Schmidt, ). Furthermore, the formation temperatures of the Myanmar jadeitites ( T < 500 °C) are significantly lower than the decarbonation conditions (Goffé et al, ; Shi et al, , ).…”
Section: Discussionmentioning
confidence: 99%